Prevalence of epstein barr virus in malignant lymphomas in Iraq - Ridha K. Walid; Al-Omer S. Lyla; Abdel-Muhymen Nidhal; Al-Hadithi H. Raji (College of Pharmacy / Mustansiriyah University, 2006)
Malignant lymphomas are among the common tumors that are associated with and may complicate Epstein Barr Virus (EBV) infection. Although the strongest association is with the endemic Burkitt lymphomas (BL), the trend of association with sporadic lymhpomas reveals a consistently increasing prevalence of the virus in Hodgkin's disease (HD) in recent years compared to the non-Hodgkin type (NHL) which may point to a possible role for the virus in the predisposition and etio-pathogenesis of the disease. evaluate the association of EBV with Hodgkin's and non-Hodgkin lymphomas in relation to age, sex and HD subtype retrospectively using archival tissue biopsy sections. Method: EBV was detected by In Situ Hybridization (ISH) using EBERs RNA probes in paraffinembedded tissue sections prepared from archival tissue biopsy blocks. (a) EBV was detected in 25 of 40 HD cases (62.5%), 9 of 30 (30%) NHL cases, 4 of 10 (40%) BL cases, and in 5 of 20 (25%) other (non-BL) NHL cases. (b) Among the EBV-positive HD cases, 19 (76%) were of the mixed cellularity (MC) subtype, 1 (4%) of the Nodular Sclerosis (NS) subtype, 1 (4%) of the Lymphocyte Predominance (LP) subtype and 4 (16%) cases were of the Lymphocyte Depletion (LD) subtype. (c) Age distribution of HD cases revealed a bi-modal pattern characterized by an early major peak (67.5% of cases) below 35 years and a minor peak (32.5% of cases) above the age of 40. On the contrary, NHL cases revealed a nearly even age distribution (43.3% versus 56.6%) below and above the age of 40, respectively. (d) No difference was observed in the incidence of HD between males and females where the ratio was close to 1:1. On the other hand, a slight male predominance was seen among NHL cases with a male to female ratio of 2:1. (a) the prevalence rate of EBV infection was high among HD cases and fell within the prevalence rates found in previous similar studies revealing a range of values from 20 to 90%. (b) the higher prevalence of EBV positivity in HD compared to NHL found in this study points to a more substantial role for the virus in the pathogenesis of former compared to the latter disease which also comes in agreement with the greater environmental element compared to the genetic element in the etiology of HD. (c) The unexpected high EBV positivity in the LD subtype of HD may be interpreted as result of the progression of some of the early less aggressive MC-HD cases to the advanced more aggressive LDHD subtype. (d) the bi-modal age distribution of EBV-positive HD cases follows the same pattern of distribution of the disease in general and testifies for the influence of environmental factors in the incidence of the disease.